THE EFFECT OF CASH TURNOVER, INVENTORY TURNOVER AND RECEIVABLES TURNOVER ON PROFITABILITYAT A FOOD AND BEVERAGES COMPANY ON THE INDONESIAN STOCK EXCHANGE - Ristati; Sri Wahyuni; Chairil Akhyar; Halida Bahri (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This study aims to examine the Influence of Cash Turnover, Inventory Turnover, and Accounts Receivable Turnover on Profitability in Food and Beverage Companies listed on the Indonesia Stock Exchange. The data used in this study is secondary data from 18 companies over six years. The method used to analyze the relationship between independent variables and dependent variables is the multiple linear regression analysis method. The results show that Cash Turnover has a positive and significant influence on profitability in Food and Beverage Companies listed on the Indonesia Stock Exchange, Inventory Turnover has a positive and significant influence on profitability in Food and Beverage Companies listed on the Indonesia Stock Exchange, and Accounts Receivable Turnover has a positive and significant influence on profitability in Food and Beverage Companies listed on the Indonesia Stock Exchange.